(untitled) (Comparative & International Education Series, 2021)
Research on American students’ academic decision-making primarily focuses on the role of academic passion in a student’s choice of major or graduate program. Recent scholarship also acknowledges the importance of parental influence in this decision-making process, particularly for international students from collectivist cultures. Previous studies, however, fail to account for other factors. Through 31 interviews with European American, Chinese American, and Chinese international undergraduate and graduate students, this study seeks to better understand other factors at work in academic decision-making. Although passion influenced European American students’ decision-making and parenting influenced their Chinese international peers, financial security, desire to impact communities, peer influence, and self-efficacy also played prominent roles. These findings suggest that mainstream academic advising, which continues to emphasize academic passion, does not match the motivations of U.S. universities’ increasingly diverse students. By acknowledging these other factors, university advisors may better support diverse students in their academic decision-making.